2022
DOI: 10.1038/s41378-022-00362-6
|View full text |Cite
|
Sign up to set email alerts
|

Raindrop energy-powered autonomous wireless hyetometer based on liquid–solid contact electrification

Abstract: Triboelectric nanogenerators (TENGs) can directly harvest energy via solid–liquid interface contact electrification, making them very suitable for harvesting raindrop energy and as active rainfall sensors. This technology is promising for realizing a fully self-powered system for autonomous rainfall monitoring combined with energy harvesting/sensing. Here, we report a raindrop energy-powered autonomous rainfall monitoring and wireless transmission system (R-RMS), in which a raindrop-TENG (R-TENG) array simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 49 publications
(52 reference statements)
0
32
0
Order By: Relevance
“…It can be seen from Figures c,d that as the concentration of KCl increased from 0 to 1 mol/L, the values of V oc and I sc decreased from <40 V to 2.5 V and 1 μA to 0.12 μA, respectively, and a similar trend also appears in NaCl solution. Previous studies have shown that the introduction of ions can reduce the electron transfer between liquid and solid surfaces, suggesting that salt solutions will lead to a significant reduction in electrical output performance. , …”
Section: Resultsmentioning
confidence: 99%
“…It can be seen from Figures c,d that as the concentration of KCl increased from 0 to 1 mol/L, the values of V oc and I sc decreased from <40 V to 2.5 V and 1 μA to 0.12 μA, respectively, and a similar trend also appears in NaCl solution. Previous studies have shown that the introduction of ions can reduce the electron transfer between liquid and solid surfaces, suggesting that salt solutions will lead to a significant reduction in electrical output performance. , …”
Section: Resultsmentioning
confidence: 99%
“…Traditional rain gauges have some disadvantages, such as complex mechanical structures, high maintenance costs, and environmental pollution [ 55 ]. Xu et al reported a new rain gauge system, which was powered by raindrops (shown in Figure 3 d) [ 56 ]. The system can harvest the raindrop energy and serve as a rainfall sensor.…”
Section: The Application Of a Self-powered Wireless Sensor Based On Tengmentioning
confidence: 99%
“…( d ) A raindrop energy-powered autonomous rainfall monitoring and wireless transmission system. Reproduced with permission [ 56 ]. Copyright 2022, Springer Nature.…”
Section: The Application Of a Self-powered Wireless Sensor Based On Tengmentioning
confidence: 99%
“…Due to the alternating current output of the transistor-inspired structure, full-wave rectification is commonly required to achieve effective energy harvesting. In conventional array designs, every droplet energy harvester cell is equipped with a full-wave rectifier, 32 causing high cost and inconvenience in fabrication and maintenance. Furthermore, for array/panel integration, we cannot take it for granted that the total power output is the product of the number and power output of each droplet energy harvester cell.…”
Section: Introductionmentioning
confidence: 99%